Análise da evolução do processo de fratura de componentes impressos 3D - (:unkn) unknown (Universidade Federal do Pampa, 2024)
The Acoustic Emission (AE) technique allows the capture of elastic waves produced by internal defects in the material, such as cracks. These waves propagate through the material and are captured by sensors distributed across the surface of the sample, generating so-called AE events. This methodology is widely used in monitoring damage to structures and serves as a tool for predicting failures in small and large structures. In the present work, the acoustic emission technique is applied to 3D printed specimens under three-point bending with ABS. The specimens have notches at three different points along their length. EA signals are obtained through Micro-Electro-Mechanical Systems (MEMS) sensors, which use a new manufacturing technology. The objective of the work is to monitor the evolution of damage through the b-value, a parameter commonly used to identify critical stages, that is, collapse in structures. The results show that MEMS sensors are promising for use in the EA technique, making it possible to identify critical points before the failure of 3D printed structures through the data collected.
Keywords: Engenharia mecânica; Emissão acústica; Sistemas microeletromecânicos; Impressão 3D; Mechanical engineering; Acoustic emission; Micro-electro-mechanical systems; 3D-printed; CNPQ::ENGENHARIAS